AI-Based Digital Literacy Development Strategy in Preparing Students to Be Globally Competitive: A Case Study at the Institute of Islamic Religion At Taqwa Bondowoso - Hadi, Mokhamad Yaurizqika; Muhlishoh, Humairoul (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
This research formulates a strategy for developing AI-based digital literacy to prepare globally competitive students at At Taqwa Bondowoso Islamic Institute. Digitalization in higher education is an urgent need so that graduates have skills according to the demands of the times. A qualitative method with a case study approach was used through interviews, observation, and documentation. The results found three main strategies: (1) increasing digital literacy for the entire academic community, (2) integrating an information and communication technology-based curriculum that supports religious knowledge and global skills, and (3) institutional collaboration with external parties to support digital transformation. The implementation of this strategy is expected to create religious higher education institutions that are adaptive to the digital era and produce globally competitive graduates.